Direct optical excitation of two and three magnons in α-Fe₂O₃ - Tanabe, Y.; Fujimaki, Y.; Kojima, K.; Uchida, S.; Onari, S.; Matsuo, T.; Azuma, S.; Hanamura, E. (Физика низких температур, 2005)
Direct excitation of two and three magnons is observed in midinfrared absorption and Raman
scattering spectra of α-Fe₂O₃ crystals. These polarization characteristics and the spectra themselves
are shown to be understood from group-theoretical point of view. The microscopic mechanism
of three-magnon excitation is proposed in addition to that of well-known two-magnon excitation
process.